Noutăți în redactarea prescripțiilor medical veterinare / News in writing veterinary medical prescriptions - Romeo Teodor Cristina (Medicamentul Veterinar, 2022)
Prescription by veterinarians of narcotic and psychotropic substances and preparations regulated by Law no. 339/2005 regarding the legal regime of narcotic and psychotropic plants, substances, and preparations, as well as those that fall under Law no. 143/2000 on the prevention and combating of drug trafficking and illicit drug consumption is done exclusively on the formulation with a special regime. In addition, national legislation through Order 128/2021 (Prescription with the special regime) and Joint Order 1328/56/2022 regulates the way of issuing prescriptions in community pharmacies of medicines for human use on veterinary prescriptions, with the aim of being used in animals. For a wider dissemination, in this paper the essential ideas presented in the SNEC-2022 continuing education courses, by the author, are presented